Las piedras de la memoria (II): El uso en época romana de espacios y monumentos sagrados prehistóricos del Sur de la Península Ibérica - García Sanjuán, Leonardo; Garrido González, Pablo; Lozano Gómez, Fernando (Complutum, 2007)
This paper tackles the analysis of a series of cases of reutilisation in Roman times of prehistoric sacred spaces and monuments, recorded throughout the South of the Iberian Peninsula. The cases under study are grouped in three main categories: (i) spatial proximity or overlapping of prehistoric and Roman burial areas, (ii) reutilisation of the inner and outer spaces of prehistoric mortuary chambers, and (iii) re-use of rock art sanctuaries and prehistoric stelae. As a conclusion, we suggest, firstly, the need to reconsider the recording criteria by which the appearance of later materials in old monuments is archaeologically assessed; secondly, we point out the need to look at these cases from the viewpoint of the elements of tradition and memory that some old sacred sites convey for the Iberian-Roman populations. Finally, we suggest these cases must be interpreted in terms of religious and political ideology.